(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Social and material inequalities have often formed the bases on which the largest social movements have emerged. In the West, for example, we see a history of robust social movements organized around labor, gender, and race. Each of these categories represents not only a group of people wishing to improve their lot, but also a systemic social division in which one group is allocated less than another. The structural approach to social movements brings to the forefront of analysis the institutionalized injustices and inequalities over which contested politics are fought.Social movement actors form organizations to influence states and institutions. These structural elements of activism are of primary interest to structural approaches to the study of social movements. Inequalities of political access have motivated some of the largest and most successful social movements in India.Structural approaches to social movements, in short, can be seen to cover an enormous terrain that takes us from questions about the nature and causes of inequality to the creation of social groupings to the causes of institutional change. Two concepts that have emerged from what is largely a state-centric body social movements research—political contexts and mobilizing structures—provide useful analytical tools for helping scholars analyze the ways states and other actors and structures shape social movement dynamics.We emphasize a global perspective in our discussion of the structural approaches to social movements, because we find it increasingly difficult to ignore the ways that national states are embedded within broader sets of relationships to other states and to global institutions.